MiR-320b and miR-320d as Biomarkers to Predict and Participate in the Formation of Platinum Resistance in Ovarian Cancer Patients - Liu, Yuan-Yuan; Zhao, Ren-Feng; Liu, Chao; Zhou, Jie; Yang, Liu; Li, Li (Frontiers in Oncology, 2022)
Ovarian cancer patients receiving platinum-based chemotherapy frequently appear platinum-resistant and tumor recurrence, eventually lead to death. Therefore, the underlying mechanisms and biomarkers are urgent to discover. In the present study, 51 platinum-resistant and 70 platinum-sensitive ovarian cancer patients were enrolled. We screened the GSE131978 dataset in the NCBI GEO database and completed microRNA chip analysis for differentially expressed lncRNAs, microRNAs, and mRNAs between platinum-resistant and platinum-sensitive patients. After filtering by Pearson correlation analysis, the competitive endogenous RNA (ceRNA) networks were subsequently constructed. Then KEGG and GO enrichment analysis about mRNAs in ceRNA networks were accomplished. More importantly, we demonstrated the differentially expressed microRNAs using quantitative real-time PCR (RT-PCR) and Fluorescence in situ hybridization (FISH). The receiver operating characteristic (ROC) curve and survival analysis were utilized to evaluate the viability of microRNAs as biomarkers to predict platinum-resistant and tumor recurrence. Results revealed that miR-320b and miR-320d have high area under the curve (AUC) values with 0.757 and 0.702 respectively, meanwhile, they probably participated in the regulatory mechanisms of platinum-resistant. Collectively, ceRNA networks including miR-320b and miR-320d reported in our study provided novel insights for platinum-resistant in ovarian cancer patients.